Surface molecular engineering of CsPbBr3 perovskite nanosheets for high-performance photodetector. (January 2022) - Yang, Bo; Bi, Wentuan; Jin, Fengxian; Ma, Xiaojia; Guo, Sheng-Qi
Abstract: Photodetectors that can directly convert optical signals into electrical signals offer great application prospects in next-generation optoelectronic nanodevices. But to-date, unsatisfactory light absorption and charge carrier separation efficiency still limit their applications. Herein, we developed a facile and low-cost surface molecular engineering strategy to construct high-performance photodetector with CsPbBr3 perovskite nanosheets. Because of the improved optical absorption and charge transfer behavior, CsPbBr3 /poly(3-hexylthiophene) (P3HT) film photodetector presents a fast response speed, excellent stability and reproducibility. We anticipate that our results not only demonstrate the effectiveness of surface molecular engineering in film photodetector design, but also provide a facile and cost-effective strategy applicable for broadband light optical sensor production. Graphical abstract: We developed a facile and low-cost surface molecular engineering strategy to construct high-performance photodetector with CsPbBr3 perovskite nanosheets. Because of the improved optical absorption and charge transfer behavior, CsPbBr3 /poly(3-hexylthiophene) (P3HT) film photodetector presents a fast response speed, excellent stability and reproducibility. Image 1 Highlights: Surface molecular engineering was put out to modified CsPbBr3 perovskite nanosheets. A facile and low-cost surface molecular engineering strategy was propose to construct high-performance photodetector with CsPbBr3 perovskite nanosheets. CsPbBr3 /poly(3-hexylthiophene) (P3HT) film photodetector presents a fast response speed, excellent stability and reproducibility due to the improved optical absorption and charge transfer behavior.